Naturally occurring polyphenols as building blocks for supramolecular liquid crystals – substitution pattern dominates mesomorphism. Issue 5 (24th March 2021) - Balszuweit, Jan; Blanke, Meik; Saccone, Marco; Mezger, Markus; Daniliuc, Constantin G.; Wölper, Christoph; Giese, Michael; Voskuhl, Jens
Abstract : The use of naturally occuring polyphenols as hydrogen bond donors in supramolecular liquid crystals was investigated using alkylated azopyridines or stilbazoles as hydrogen bond acceptors. Abstract : A modular supramolecular approach towards hydrogen-bonded liquid crystalline assemblies based on naturally occurring polyphenols is reported. The combination of experimental observations, crystallographic studies and semi-empirical analyses of the assemblies provides insight into the structure–property relationships of these materials. Here a direct correlation of the number of donor OH-groups as well as their orientation with the mesomorphic behavior is reported. We discovered that the number and orientation of the OH-groups have a stronger influence on the mesomorphic behavior of the supramolecular assemblies than the connectivity ( e.g. stilbenoid or chalconoid) of the hydrogen bond donors. Furthermore, the photo-switching behavior of selected complexes containing azopyridine ligands was investigated. This study will help future scientists to gain a deeper understanding of the underlying mechanisms and structure–property relationships of supramolecular assemblies with mesomorphic behavior, which is still one of the major challenges in current science.